2007
DOI: 10.1080/08985620701440007
|View full text |Cite
|
Sign up to set email alerts
|

Do different institutional frameworks condition the influence of local fear of failure and entrepreneurial examples over entrepreneurial activity?

Abstract: This paper analyses how different institutional frameworks condition the influence of selected social traits: the social stigma to entrepreneurial failure and the presence of entrepreneurial role models, over entrepreneurial activity levels in a rural area with strong industrial and entrepreneurial history versus those that are not necessarily characterized by such a tradition. To attain this objective we undertake a rare events logit model using a robust Spanish dataset from 2003. The main contribution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
216
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(237 citation statements)
references
References 54 publications
11
216
0
10
Order By: Relevance
“…The GEM fear of failure question is, to the best of our knowledge, the only available measure of fear of failure in large-scale datasets and has already been successfully used in previous studies. For example, Arenius and Minniti (2005) and Vaillant and Lafuente (2007) find that those individuals who reveal fear of failure are much less likely to be engaged in entrepreneurship.…”
Section: Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…The GEM fear of failure question is, to the best of our knowledge, the only available measure of fear of failure in large-scale datasets and has already been successfully used in previous studies. For example, Arenius and Minniti (2005) and Vaillant and Lafuente (2007) find that those individuals who reveal fear of failure are much less likely to be engaged in entrepreneurship.…”
Section: Dependent Variablementioning
confidence: 99%
“…Firstly, the individual perception of entrepreneurship is an important determinant for subsequent entrepreneurial activity. In particular, fear of failure has a strong negative relationship with entrepreneurial entry (e.g., Arenius and Minniti, 2005;Vaillant and Lafuente, 2007;Stuetzer et al, 2014). One explanation for this negative relationship comes from research on achievement orientation showing that avoiding failure is a strong human motivation (e.g., Conroy and Elliot, 2004;Elliot and Harackiewicz, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, Cardon et al (2011) showed that even within the US, entrepreneurs in certain regions still experience stigmatization due to venture failure. Vaillant and Lafuente (2007) concluded that belief in the social stigma of entrepreneurial failure is a significant deterrent to entrepreneurial activity in Spain. Damaraju et al (2010) compared collectivist and individualistic cultures and found collectivist cultures were less tolerant and more stigmatizing of failure thereby discouraging entrepreneurial risk taking.…”
Section: Background Literaturementioning
confidence: 99%
“…It is therefore necessary to take into account that some socio-cultural practices, values and norms lead more to encourage entrepreneurship and others to inhibit it (Krueger, Liñán, & Nabi, 2013). According to Vaillant and Lafuente (2007) the formal factors (rules and regulations) are practically equivalent in all the Spanish regions. Therefore, following the idea of North (1990) the differences could be found rather in the informal factors (attitudes, beliefs and values) than in the formal ones.…”
Section: María Huertas Gonzalez-serrano Ferran Calabuig Moreno Jerómentioning
confidence: 99%